2016
DOI: 10.1016/j.bjane.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral greater occipital nerve block for treatment of post-dural puncture headache after caesarean operations

Abstract: Treatment of PDPH with GON block seems to be a minimal invasive, easy and effective method especially after caesarean operations. A GON block may be considered before the application of a blood patch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…A study of greater occipital nerve block for the treatment of PDPH showed beneficial effects in reducing pain severity, although the evidence is limited. Several authors have suggested its use as an alternative to an epidural blood patch since it is less invasive and leads to prompt symptom relief [8586]. …”
Section: Treatmentmentioning
confidence: 99%
“…A study of greater occipital nerve block for the treatment of PDPH showed beneficial effects in reducing pain severity, although the evidence is limited. Several authors have suggested its use as an alternative to an epidural blood patch since it is less invasive and leads to prompt symptom relief [8586]. …”
Section: Treatmentmentioning
confidence: 99%
“…[24] Furthermore, the efficacy of the block also has been shown in the post-dural puncture headache. [25,26] We have emphasized in our study that one of the causes of the headache might be lumbar spinal drainage. In this case, we think that headache is caused by a similar mechanism with post-dural puncture headache.…”
Section: Although Aneurysmatic Sah Patients Treated Withmentioning
confidence: 70%
“…Bilateral greater occipital nerve block (BGON) has been reported for the successful treatment of PDPH [3][4][5]. Authors suggest that treatment of PDPH with BGON block seems to be a minimally invasive, easy and effective method and may be considered before the application of a blood patch [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral greater occipital nerve block (BGON) has been reported for the successful treatment of PDPH [3][4][5]. Authors suggest that treatment of PDPH with BGON block seems to be a minimally invasive, easy and effective method and may be considered before the application of a blood patch [5]. The analgesia obtained after the BGON block may be explained by the central neuromodulatory effect that causes decreased central sensitization due to the temporary interruption of afferent input to the dorsal roots and trigeminal nucleus [5,6].…”
Section: Introductionmentioning
confidence: 99%